KKN-PPM: Pemberdayaan Masyarakat Pengelolaan Sanitasi Air Bersih pada Kawasan Perdesaan Prioritas Nasional di Desa Loeha Kecamatan Towuti - Andi Silfiana; Sugiyanto Sugiyanto; Chrecencya Nirmalarumsari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Real Work Lecture Program-Community Empowerment Learning (KKN-PPM) STIKES Bhakti Pertiwi Luwu Raya Palopo is one of the community service activities carried out routinely by universities. The KKN PPM concept is intended to change the concept of